(untitled) (Fiep Bulletin - online, 2019)
The regular practice of physical activity since childhood and adolescence is associated with physical andpsychological benefits in the short and long term. The physical education teacher is a fundamental factor to encourage physicalactivity, which is directly related to the improvement and maintenance of health. This study aims to analyze the relationshipbetween health incentive and physical education teacher from 2014 to 2018, through a systematic review. The methodology usedwas based on the application of the InOrdinario equation, resulting in 23 articles for analysis. The results emphasize aspects suchas the importance of the physical education teacher, both in schools and in public health, and its relationship with the preventionof diseases. We conclude that the greater the intensity and frequency of physical activity, the health conditions will be expanded,as well as the prevention of diseases. The physical education teacher plays a fundamental role in encouraging health, in whatrefers to the performance in schools and even in public health, since its activities promote improvement and maintenance of thehealth of children, adolescents and adults, either through the implementation of related programs health, investing in training, oracting in the public healthcare system.